2012
DOI: 10.1155/2012/301818
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Synchronized Nasal Intermittent Positive Pressure Ventilation for Infants <32 Weeks' Gestation with Respiratory Distress Syndrome

Abstract: Aim. To evaluate whether synchronized-NIPPV (SNIPPV) used after the INSURE procedure can reduce mechanical ventilation (MV) need in preterm infants with RDS more effectively than NCPAP and to compare the clinical course and the incidence of short-term outcomes of infants managed with SNIPPV or NCPAP. Methods. Chart data of inborn infants <32 weeks undergoing INSURE approach in the period January 2009–December 2010 were reviewed. After INSURE, newborns born January –December 2009 received NCPAP, whereas those b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…Our clinical observations [14,29,31] are consistent with laboratory data [16] and show that the Giulia® flow-trigger is reliable to provide SNIPPV for treatment of neonatal respiratory failure. From clinical trials, SNIPPV seems more effective than NIPPV and NCPAP in reducing need for intubation in RDS, in improving the success of extubation and in treating apnea of prematurity, with a reassuring absence of relevant side effects.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our clinical observations [14,29,31] are consistent with laboratory data [16] and show that the Giulia® flow-trigger is reliable to provide SNIPPV for treatment of neonatal respiratory failure. From clinical trials, SNIPPV seems more effective than NIPPV and NCPAP in reducing need for intubation in RDS, in improving the success of extubation and in treating apnea of prematurity, with a reassuring absence of relevant side effects.…”
Section: Discussionsupporting
confidence: 85%
“…In 2007, a trial by Bhandari et al [28] confirmed the beneficial effects of SNIPPV for VLBW infants with RDS and the lower incidence of BPD among those treated with this technique compared to MV. We conducted a study using flow-SNIPPV as the primary mode of ventilatory support in infants <32 weeks' gestation with RDS [29]. The aim of the trial was to evaluate whether flow-SNIPPV, used immediately after the INSURE technique, was effective in further reducing the incidence of MV when compared to the conventional INSURE/NCPAP treatment.…”
Section: Clinical Results With Snippvmentioning
confidence: 99%
“…Until present, two devices have been commonly used to trigger the ventilator during NIV in preterm infants: the abdominal capsule,29–32 and the flow sensor 17 33 34. Recently, a device using a diaphragmatic electromyogram has been introduced, however little data are available on clinical outcomes35 The abdominal capsule, although quite effective, has some disadvantages relating to the high sensitivity to the infant's spontaneous movements and to the considerable skill required for correct placement.…”
Section: Discussionmentioning
confidence: 99%
“…While there are some encouraging non-randomised data [54], RCTs comparing NIPPV or BiPAP with NCPAP have failed to show a convincing effect on BPD. Although nine RCTs have included BPD as a secondary outcome, none of these trials were powered to detect differences in BPD rates.…”
Section: Later Outcomes Following Nippvmentioning
confidence: 99%